PENGARUH BIMBINGAN DAKWAH BALAI REHABILITASI SOSIAL (BRS) WATUNAS â€œMULYA JAYAâ€ JAKARTA TERHADAP PEMBENTUKAN KARAKTER KEMANDIRIAN MANTAN WANITA TUNA SUSILA BINAANNYA - Ahmad Suhdi; Imang Maulana (Institut Agma Islam Hamzanwadi NW Lombok TImur, 2023)
Social problem is social symptom which frequently appears in community life. This is in the contrary with the prosperity and social norm. Social problem which frequently occurs in the community one of which is prostitution problem namely there are many prostitute women (WTS) who harm the community environment, the government, and also individuals who do social deviation. One of which is the lack of independence character guidance on the prostitute women until they do everything possible for the sake of sustaining their life. Based on this background the researcher was interested to investigate the influence of da’wah on former prostitute women at Social Rehabilitation Office (BRS) Watunas Mulya Jaya Jakarta. The purpose of this research was to find out the da’wah influence of Social Rehabilitation Office (BRS) Watunas Mulya Jaya Jakarta on former prostitute women. The researcher employed quantitative approach with survey research type based on questionnaire. The technique of sample selection employed census sampling technique. In the case of data analysis, the researcher employed validity test and reliability test using pearson’s correlation product moment, normality test, linearity test, determination coefficient test, simple regression analysis test, and hypothesis test (ANOVA). The results of this research showed that there was influence of Da’wah guidance by Social Rehabilitation Office (BRS) Watunas Mulya Jaya Jakarta on the independence character formation on former prostitute women seen from the result of hypothesis test with significance value obtained namely 0,000 or <0,05 until Ho was rejected and H1 was accepted. Also based on determination coefficient test, it was found out that the size of influence of da’wah guidance on independence character of respondents obtained r square in the amount of 62,7%.